Educomunicación y plataformas multimedias - López Delgado, Cinthya Cristina (2024)
The general objective of this study is to determine the mastery that teachers have in the use of podcast multimedia platforms as a pedagogical tool applied in education, using a mixed approach methodology, with descriptive scope. The data was collected through a survey of a sample of 55 students of the 5th semester of social communication at UNEMI based on convenience sampling, complementing this information with an interview with three teachers of the same career with knowledge in radio production and the use of the podcast. The results showed that, although there are teachers who demonstrate solid mastery in the use of the podcast as a pedagogical tool, specifically those interviewed, it is also clear that there are educators who have difficulties in using it, either due to fear of changing their methodology. of teaching, the lack of knowledge in its management, scarce resources, the time required for its production, the restrictions of the academic schedule and the resistance that students may demonstrate with respect to participating in classes. Therefore, educators must improve their skills and knowledge associated with its use, while encouraging students to participate in its design and production, which will promote their learning, without ignoring other advantages such as facilitating the understanding of the contents they address and make of teaching-learning a more entertaining process that favors the development of knowledge by students.